Особливості формування електролітичних покриттів на основі сплавів кобальту - Ненастіна, Тетяна Олександрівна; Проскуріна, Валерія Олегівна; Ведь, Марина Віталіївна; Горохівська, Наталя Валентинівна (Київський національний університет технологій та дизайну, 2020)
The possibility of electrosynthesis and composition / surface morphology control of electrolytic coatings based on cobalt alloys with refractory metals by varying the electrolysis parameters is proved. The scattering capacity characteristics and specific conductivity of deposition electrolytes of Co-Mo-WOx and Co-Mo-ZrO2 coatings are established. The composition and morphology of Co-Mo-WOx, Co-Mo-ZrO2, Co-Mo-W-V and Co-Mo-Zr-V coatings were determined. It is established that incompletely reduced oxides of the refractory metals are included into the coatings composition, which allows to position them as composite.
Features of Cobalt Alloys Based Electrolytic Coatings Formation
Keywords: composite coatings; cobalt; conductivity; scattering ability; vanadium; композитні покриття; кобальт; провідність; ванадій; гальванічні покриття; електрохімічні методи; сплави металів